The Prevalence and Investigation of Risk Factors of Oral Mucositis in a Pediatric Oncology Inpatient Population; a Prospective Study. Issue 1 (January 2018) - Allen, Gabrielle; Logan, Richard; Revesz, Tom; Keefe, Dorothy; Gue, Sam
Abstract : Background: Oral mucositis can be a frequent and severe complication of chemotherapy in children. It can result in pain, infection, depression, prolonged admission, treatment delays, increase in patient morbidity, and increased costs. Aim: To record the prevalence and severity of oral mucositis among inpatients and explore the relationship of risks factors and the development of oral mucositis. Design: During an 18-month period 643 clinical inpatient assessments were completed on 73 children who were admitted and had received chemotherapy in the last 14 days. Results: There were 43 episodes of oral mucositis in 31 children; 42.5% of the inpatient population. World Health Organization assessment identified 32.6% of episodes were grade 1, 34.9% grade 2, 14.0% grade 3, and 18.6% grade 4. Analysis revealed significant associations between patient diagnosis ( P <0.0001), chemotherapy cycles ( P <0.0001), day 8 and 9 of the chemotherapy cycle ( P <0.05), and neutropenia ( P <0.0001) and oral mucositis. Children had increased length of admission with increasing severity of oral mucositis ( P =0.0005). Conclusions: The prevalence of oral mucositis was 42.5% among inpatients and admission length was increased with increasing severity. Patient diagnosis, chemotherapy treatment block, day of chemotherapy cycle, and neutropenic status were shown to influence the risk of developing oral mucositis.